21q22.11q22.12 deletion syndrome with secondary hemophagocytic lymphohistiocytosis - Taneja, Sunil; Bansal, Alexandra; Goyal, Pratishtha; Khan, Iltefat; Shekhar, Rajeev; Khan, Iftikhar Hussain (International Journal of Contemporary Pediatrics, 2021)
Haemophagocyticy lymyphohistiocytosis in the new-born is uncommon. Incidence is reported between 1 in 50,000 to 1,50,000 admissions. Usually it is primary or familial HLH in the first year of life. Secondary causes are due to viral, bacterial and fungal infections. A dysmorphic small for gestational age male neonate presented with sepsis and neonatal cholestasis. He also had associated HLH. Exom sequencing showed a 21q22.11q22.12 deletion. This has not known to have any association with familial HLH. He was managed with IVIG and steroids. The neonate made a recovery but succumbed later to an intercurrent illness.